Pengaruh konsentrasi Ca(OH)2 dan suhu pemasakan pada proses nikstamalisasi tepung jagung - Sri Winarti; Ratna Yulistiani; Tuty Shohibatuz Zakiyah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Nixtamalization is a corn cooking process with the addition of calcium hydroxide. This study aims to determine the best treatment combination between the concentration of Ca(OH)2 and cooking temperature to changes in physicochemical properties and amylographic properties of cornflour. This research was conducted using a completely randomized design with a factorial pattern with two factors. Factor I: concentration of Ca(OH)2 1%, 2% and 3% (w/v); Factor II: cooking temperature 70️℃, 80️℃, 90️℃, and 100️℃. The results of data analysis using ANOVA for all parameters showed significant differences. The results showed that the best treatment combination was the nixtamalization treatment with a concentration of Ca(OH)2 2% and a cooking temperature of 90️℃ which produces cornflour with a color coordinate value L*; a*; b* is 68.64; 16.27; 45.22; calcium content 0.473%; amylose content 68.92%; swelling power 7.13 ml/g; freeze-thaw stability 0.211 g/g. The microscopic structure of the best treatment showed that the surface shape of the starch granules was slightly rough, the cell walls were slightly thicker than the control corn flour; amylographic properties showed gelatinization temperature of 78.15️℃; peak gelatinization time of 8.13 minutes; peak viscosity 1147 cP; hot paste viscosity 1056 cP; breakdown viscosity 91 cP; final viscosity 2132 cP; setback viscosity 1076 cP.